Removal of a Trigger Cord Stuck between Bands during Endoscopic Multiple-Band Ligation for Treating Esophageal Variceal Hemorrhage - Nam Seok Ham; Danbi Lee; Sung Hyun Won; Jeongseok Kim; Seokjung Jo; Sangyoung Yi; Seol So (Korean Society of Gastrointestinal Endoscopy, 2020)
Endoscopic variceal ligation is the preferred endoscopic treatment method for esophageal variceal bleeding. The incidence of complications such as chest pain, bleeding, stricture formation, and aspiration pneumonia is low. We report a case wherein a malfunctioning multiple-band ligator could have potentially caused damage to the esophageal varices and massive bleeding. The equipment was safely removed using scissors and forceps. To the best of our knowledge, this is the first published report detailing the management of a case of esophageal variceal bleeding.